The Environmental Awareness in the Context of Sustainable Development: A Scale Development and Reliability Study - Fatime Balkan Kıyıcı; Elif Atabek-yiğit (Sakarya University Journal of Education)
Sustainable development, with its roots dating back 35 years, is gaining more and more importance, and it states that meeting the needs of the present must also take into account the ability of future generations to meet their needs. To realize sustainable development, that has environmental, economic, and social dimensions; there are activities of various institutions and organizations as well as the work of governments. It is known that environmental education will contribute to individuals in terms of taking important responsibilities in the construction of our future and creating awareness, knowledge, and awareness of ecology and the environment. In this study, a scale for environmental awareness in the context of sustainable development was developed. The sample of the study consists of 492 secondary school students. The scale development process, which started with the preparation of the item pool, continued with the necessary analyzes and eventually resulted in the acquisition of a valid and reliable measurement tool consisting of 2 factors and 15 items. It is expected that the developed scale will contribute to the literature for evaluating environmental activities, projects, or instructional designs in the context of sustainable development.